THE RISE OF THE EAST AND THE FAR EAST: GERMAN LABOR MARKETS AND TRADE INTEGRATION. Issue 6 (29th July 2014) - Dauth, Wolfgang; Findeisen, Sebastian; Suedekum, Jens
Abstract We analyze the effects of the unprecedented rise in trade between Germany and "the East" (China and Eastern Europe) in the period 1988–2008 on German local labor markets. Using detailed administrative data, we exploit the cross‐regional variation in initial industry structures and use trade flows of other high‐income countries as instruments for regional import and export exposure. We find that the rise of the East in the world economy caused substantial job losses in German regions specialized in import‐competing industries, both in manufacturing and beyond. Regions specialized in export‐oriented industries, however, experienced even stronger employment gains and lower unemployment. In the aggregate, we estimate that this trade integration has caused some 442, 000 additional jobs in the economy and contributed to retaining the manufacturing sector in Germany. This is almost exclusively driven by the rise of Eastern Europe, not by China. We also conduct an analysis at the individual worker level, and find that trade had a stabilizing overall effect on employment relationships.